Penerapan Buku Cerita Interaktif Untuk Meningkatkan Kemampuan Membaca Siswa Kelas V SD Inpres 2 Tondo - vhirly_ (JURNAL DIKDAS, 2026)
This study aims to describe ways to improve the reading skills of fifth-grade students at SD Inpres 2 Tondo through interactive storybooks. This study was motivated by the low reading skills of fifth-grade students at SD Inpres 2 Tondo. This was observed from the initial observation of 30 fifth-grade students, only 19 of whom were categorized as very good. Therefore, a method is needed to improve the reading skills of students. This study used classroom action research, which consists of the stages of planning, action, observation, and reflection. The research data was collected using the observation method, with instruments in the form of questionnaires and teacher and student activity sheets. The results of the study show that the reading ability of students in cycle I reached an average of 76.3%. Then in cycle II, it increased to 81.0%. The contribution of the application of interactive storybook learning media to improving students' reading ability was very significant, meaning it was in the high category. From the results of the study, it can be concluded that actions using picture storybooks can improve students' reading ability